Innovative technologies in virgin olive oil extraction process: influence on volatile compounds and organoleptic characteristics. (3rd July 2019) - Caponio, Francesco; Leone, Alessandro; Squeo, Giacomo; Tamborrino, Antonia; Summo, Carmine
Abstract: BACKGROUND: Innovative technologies are experimentally applied to the virgin olive oil extraction process in order to make it continuous and more efficient. Most of the efforts aim at overcoming the limitations of the traditional malaxation step, which, however, is essential for the development of virgin olive oil sensory notes. RESULTS: Compared to the traditional process, innovative technologies based on the heat exchanger led generally to a decrement in volatile lipoxygenase (LOX) alcohols linked to alcohol dehydrogenase activity and, conversely, to a slightly increase in volatile LOX esters. Aldehydes from the same pathway were not significantly affected. However, an industrial combined plant constructed from a heat exchanger, low‐frequency ultrasound device and microwave apparatus determined the highest 'fruity' intensity perceived by panellists, in accordance with the highest value of total volatiles, with values significantly higher than heat exchanger alone, which, instead, had the lowest levels of hexanal and LOX alcohols. The pungent taste showed the same trend observed for 'fruity' intensity, whereas bitter taste did not show significant differences among trials. CONCLUSION: The introduction of ultrasound, coupled with heat exchanger and microwave, seemed not to modify the behaviour of enzymes of the LOX pathway, and the obtained virgin olive oils showed volatiles and organoleptic characteristics not significantly different from those obtained by the traditional olive oil extraction process. These findings provided the first insights into the effect of the combination of innovative technologies in the olive oil extraction process on virgin olive oil volatiles and sensory characteristics. © 2019 Society of Chemical Industry